Mathematical Representation Ability in Terms of Students’ Learning Independence in Project Based Learning Model Assisted by Google Sites - Wulandari, Inayah; Isnarto, Isnarto (Unnes Journal of Mathematics Education, 2023)
The purposes of this study were to analyze the quality of learning mathematics in the Project Based Learning model assisted by Google Sites on mathematical representation ability, to analyze the effect of learning independence on mathematical representation ability, and to describe the mathematical representation ability in terms of learning independence in the Project Based Learning model assisted by Google Sites. The research used mixed method with sequential explanatory design. The population in this study were all grade VIII students of SMP N 22 Semarang in the 2022/2023 academic year. The sample selected in this study consisted of class VIII E as the experimental class and class VIII F as the control class. Data collection techniques used in this study were tests, questionnaires, observations, and interviews. The results of the study showed that: (1) mathematics learning with Project Based Learning model assisted by Google Sites is qualified in developing students' mathematical representation ability; (2) there is a positive effect of learning independent on mathematical representation ability in Project Based Learning model assisted by Google Sites; (3) the description of the mathematical representation ability in terms of learning independence is divided into 3 categories, namely (a) students with high learning independence are able to fulfill all indicators of mathematical representation ability; (b) students with moderate learning independence are quite able to fulfill indicators of mathematical representation ability; and (c) students with low learning independence tend to be able to fulfill indicators of mathematical representation. However, it is necessary to pay attention to students' mathematical representation abilities, one of which is that students with low learning independence should be given guidance in processing information to be able to represent problems well to facilitate better problem solving.